Control of Ectoparasitic Monogenean Infestation on GIFT Tilapia (Oreochromis sp.) using Salt Addition - Hadiroseyani, Yani; Harti, L.S.; Nuryati, Sri (Jurnal Akuakultur Indonesia, 2009)
Ectoparasitic monogenean infestation is one of fish diseases which may cause mass mortality, therefore controlling the parasites is one of the important factors to ensure the success of aquaculture activities. Salt addition is one of disease curative and controlling techniques which is cheap, easy and environmental friendly as well as effective to control ectoparasites in freshwater environment. The objectives of this study were to examine monogenean parasites species in GIFT (Genetically Improved Farmed Tilapia) tilapia, their tolerance to salt concentration and the most effective salt concentration to control the parasites. Identification, intensity and prevalence of parasitic monogenean were carried out on the external parts (body surface, fins and gills) of 31 fishes. Subsequently, two different experiments were carried out  to determine parasites and fish resistance on various salt concentration at a range of 0 - 24 g/l with an interval of 2 g/l. To confirm the results of previous experiment, parasites infected fish was immersed in salt water at various concentration based on previous experiments. Two genera of monogenean were identified in GIFT tilapia, i.e. Gyrodactylus sp. on body surface and fins, and Cichlidogyrus sp. on gills with the same prevalence (100%). The intensity of those parasites was different, namely 27.84 ind/fish for Gyrodactylus sp. and 6.06 ind/fish for Cichlidogyrus sp. The intensity of both parasites was found to be lower as salt concentration increase. Salt concentration of 24 g/l was the most effective concentration to reduce parasites infestation and could totally treat the infested fish within 6 days. Keyword : tilapia, Oreochromis, monogenea, parasite and salt     ABSTRAK Serangan monogenea ektoparasitik merupakan salah satu masalah penyakit ikan yang dapat menyebabkan kematian masal, sehingga pengendaliannya merupakan salah satu kunci keberhasilan dalam usaha budidaya. Garam merupakan agen penyembuh atau pengendali penyakit yang murah, mudah didapat, ramah lingkungan dah efektif untuk mengendalikan ektoparasit pada lingkungan air tawar. Penelitian ini bertujuan untuk mengetahui jenis monogenea yang menyerang ikan nila, kisaran toleransinya terhadap kadar garam air dan efektifitas kadar garam yang dapat menekan perkembangannya tanpa membahayakan inang. Identifikasi, intensitas dan prevalensi monogenea yang menyerang dilakukan melalui pemeriksaan eksternal (permukaan tubuh, sirip dan insang) 31 ekor ikan nila gift. Kemudian penentuan kisaran salinitas monogenea dan ikan inang dilakukan dengan menguji daya tahan parasit dan ikan pada salinitas 0 - 24 g/l dengan selang 2 dilanjutkan dengan penelitian perendaman ikan yang terinfeksi monogenea dalam air garam dengan salinitas berdasarkan hasil penelitian sebelumnya. Hasil identifikasi menunjukkan bahwa terdapat dua genus monogenea yang menyerang ikan nila yaitu Gyrodactylus sp. pada permukaan tubuh dan sirip serta Cichlidogyrus sp. pada insang dengan prevalensi mencapai 100%. Namun intensitas kedua parasit tersebut ditemukan berbeda yaitu 27,84 ind/ekor untuk Gyrodactylus sp. dan Cichlidogyrus sp. sebesar 6,06 ind/ekor. Intensitas Gyrodactylus sp. menurun dengan meningkatnya konsentrasi garam, begitu juga dengan intensitas Cichlidogyrus sp. Konsentrasi 24 g/l merupakan konsentrasi garam yang paling cepat untuk mengurangi serangan parasit tersebut pada ikan dibandingkan konsentrasi 12 dan 0 g/l. Bahkan dapat membebaskan ikan dari infeksi parasit tersebut dalam waktu hari 6 hari. Kata kunci : nila, Oreochromis, monogenea, parasit dan garam.